The German wall : fallout in Europe - Silberman, Marc, 1948- 1948- (Studies in European culture and history, 2011)
"When the Berlin Wall opened unexpectedly on November 9, 1989, it marked a rupture of global significance. For Germany's national history the event has become, next to the defeat of 1945, the most significant date in collective memory. For Cold War Europe the Berlin Wall represented a symbol of border crisis and of difference and division. This interdisciplinary volume addresses multiple consequences of the fall of the Wall: looking back at the physical barrier, its demise, and how it has been mediated in film and television; detailing the processes of restoring and revitalizing the city and the country that had been torn asunder; recognizing the new challenges of integrating socially and politically old and new minorities; and identifying how a new European identity may emerge "after the Wall." The anthology is targeted at scholars and advanced students in history, German studies, sociology, art history, and related fields"--